1997
DOI: 10.1139/y97-153
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic characteristics of endometriosis in the mouse model: application to toxicology

Abstract: Surgically induced endometriosis in the mouse has been described as a model to investigate the effect of environmental pollutants on the growth of endometriotic implants. The objectives of this study were to evaluate a modified surgical procedure to induce endometriosis and validate the model by comparing the effects of estrogen, 4-chlorodiphenyl ether (4-CDE) as a possible estrogenic contaminant, and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a contaminant with predominantly anti-estrogenic activities, on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Indeed, previous publications have shown that daily administration of estradiol or estrone by subcutaneous injection or hormone-releasing pellets significantly increases ectopic lesion size and survival [23][24][25]27] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous publications have shown that daily administration of estradiol or estrone by subcutaneous injection or hormone-releasing pellets significantly increases ectopic lesion size and survival [23][24][25]27] .…”
Section: Discussionmentioning
confidence: 99%
“…The size, surface area and dosage of particles all appear to play important roles in mediating nanoparticle toxicity. It has been proposed, for example, that the size of nanoparticles influences their adhesion to and interaction with living cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One implication of macrophages not explored by the studies in this review are the neuroimmune interactions between macrophage-induced stimulation of inflammatory cytokines and peripheral nerves (Liang et al 2018). These neuroinflammatory macrophage-nerve interactions have been strongly tied to endometriosis-related pain (Forster et al 2019;Wu et al 2017).…”
Section: Discussionmentioning
confidence: 99%